Shallot (Allium cepa Lour) Peels Snack Bar as Immunomodulator for Health Improvement in the Digital Era - Sella Paramitha; Amalia Salsa Billah Firdausi; Siti Fadilla; Faza Saiqur Rahmah; Muhammad Abbas Ar-Riziq; Mayu Rahmayanti (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
The digital era has brought many changes, both positive and negative impacts. The challenges of this digital era cover various sectors, including the health sector. One of the effects is the radiation from electromagnetic waves due to the use of cell phones that can interfere with health in the long term, such as a decrease in the immune system. This study aims to determine the secondary metabolite content of shallot peel extract and the formulation of the snack bar as a nutraceutical product with antioxidant properties. It becomes a solution to increase the immune system or immunomodulator. An evidenced by the phytochemical screening test, which gave positive results. In addition, this snack bar also positively contains essential nutrients, such as carbohydrates, protein, and fat. From the hedonic test, the snack bar formulation has the appearance of a snack bar in general, with solid consistency and brownish-yellow color, a characteristic odor of wheat, and a savory taste with a small amount of sweetness. This snack bar formulation has the potential as an immunomodulator against the decline in the immune system. The tastes of the snack bar are acceptable to the public.